2007
DOI: 10.1071/ar06188
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and opportunities in applying seasonal climate forecasts in agriculture

Abstract: Climate variability has an enormous impact on agricultural productivity, rural livelihoods, and economics at farm, regional, and national scales. An every-day challenge facing farmers is to make management decisions in the face of this climate variability. Being able to minimise losses in droughts and take advantage of favourable seasons is the promise of seasonal climate forecasts. The criteria for their adoption depends on what variables are forecast, their accuracy, the likely economic and/or natural resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 64 publications
2
61
0
Order By: Relevance
“…Some research findings have indicated the usefulness of weather forecasts for reducing vulnerability of rain-fed agriculture to drought, flooding and extremely low or high temperature [22][23][24][25][26]. Initiatives to promote access of African farmers to weather forecasts include formation of several regional Climate Outlook Forums (COFs) in the late 1990s [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Some research findings have indicated the usefulness of weather forecasts for reducing vulnerability of rain-fed agriculture to drought, flooding and extremely low or high temperature [22][23][24][25][26]. Initiatives to promote access of African farmers to weather forecasts include formation of several regional Climate Outlook Forums (COFs) in the late 1990s [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Ash et al (2007), they note that for successful adoption of SCF: (1) regions need to posses skilful and actionable forecasts, (2) regions need to be agriculturally active and support crops that are sensitive to climate variability (for the US, only the Florida peninsular and eastern and southern Texas appear to fulfil this criterion), and (3) processes need to be in place that encourage agricultural service agencies to include forecast-based decision support in their services. The authors stress the importance of participatory approaches that include all interested parties to ensure success in the development, implementation, and communication of farm-specific prediction products.…”
Section: The Scientific Outcomes From This Workhop Are Briefly Summamentioning
confidence: 99%
“…The discussion surrounding Ash et al (2007), Garbrecht and Schneider (2007), and Hayman et al (2007) highlighted the difficulties farmers have in integrating SCF into their decision making, which were echoed by Nelson et al (2007) in the policy domain. While science is geared towards providing detailed, quantitative solutions to precise questions, decision makers such as farmers and policy makers require holistic evaluations of multiple sources of risk.…”
Section: The Scientific Outcomes From This Workhop Are Briefly Summamentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an established link between global climate patterns and food price volatility [60]. Droughts in Australia and poor growing conditions in Russia, the United States and the Ukraine over several years significantly contributed to the 2008 spike in global wheat prices [28].…”
Section: Oil Price Risesmentioning
confidence: 99%